2020
DOI: 10.1007/s00167-020-05870-4
|View full text |Cite
|
Sign up to set email alerts
|

Excellent survival and outcomes with fixed-bearing medial UKA in young patients (≤ 60 years) at minimum 10-year follow-up

Abstract: Purpose To evaluate whether long-term (10-year minimum) patient outcomes and survival of ixed-bearing medial unicompartmental knee arthroplasty (UKA) in patients aged ≤ 60 years were favorable despite non-conventional age criteria. Methods The authors reviewed the records of 91 consecutive medial UKAs performed in patients aged ≤ 60 by a single surgeon. All patients received the same ixed-bearing M/G Unicompartmental Knee System. Patients records were updated, noting complications or revisions, and Oxford Knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…The overall patient satisfaction rate in our cohort was 93%, and was similar in both age groups. Several studies have reported high satisfaction in younger patients after UKA [ 15 , 17 ]. Dalury et al [ 16 ] reported satisfactory results for patients aged 46–59 years at mid-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall patient satisfaction rate in our cohort was 93%, and was similar in both age groups. Several studies have reported high satisfaction in younger patients after UKA [ 15 , 17 ]. Dalury et al [ 16 ] reported satisfactory results for patients aged 46–59 years at mid-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Dalury et al [ 16 ] reported satisfactory results for patients aged 46–59 years at mid-term follow-up. Mannan et al [ 17 ] found that 97% of the patients aged 60 years or less were pleased or very pleased after UKA at minimum 10-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of unicompartmental implants has increased in popularity over the last decades due to excellent clinical results as it facilitates minimal invasive surgery, faster recovery, and a higher postoperative knee function. Several studies have reported good joint survival and superior function following UKA, especially in young and very active patients [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of advantages of UKA, for instance, less blood loss, faster recovery, as well as improved proprioception [1,2]. It has been proven that good to excellent outcomes are found in the mid-term and long-term follow-ups in properly selected patients who underwent UKA [1,3].…”
Section: Introductionmentioning
confidence: 99%